Desain Tata Letak Gudang untuk Meminimalkan Ongkos Material Handling pada PT. Rotaryana Prima - Sri Hartini; Atikah Atikah; Tiara Tiara (eCo-Fin, 2023)
The layout of facilities that are less regular can result in an increase in costs. Placement of goods that are not appropriate and do not pay attention to the distance of movement of goods, this can cause several problems, especially in the movement of material handling. From the emergence of some of these problems, this study aims to determine the layout design of warehouse facilities and minimize material movement distances and reduce costs in material handling. The method to be used is quantitative analysis by calculating distance, frequency, material handling moments and material handling costs to determine the outcome of the redesign process. The results obtained from this study are the total cost of material handling in the initial layout of IDR 3,681,600/month with 60 m from the loading and unloading place to the warehouse and the total cost of material handling in the proposed layout is IDR 2,761,200/month with distance of 45 m from the place of loading and unloading to the warehouse